Clean energy hydrogen/fuel cells laboratory manual - Santhanam, KSV. (Singapore : World Scientific Publishing Co. Pte Ltd., 2016)
'This manual is designed for the use of hydrogen as a fuel in the fuel cells. The turn of the century has seen a realization of moving towards clean energy due to a variety of considerations ranging from global warming, anxiety to living in a healthy atmosphere, depletion of fossil fuels, oil slick in Gulf of Mexico resulting in disasters and so forth. Innumerable debates in the literature has led to the identification of hydrogen as the safest and efficient fuel over the other available fuels. This fuel can be used in two ways: a) direct combustion like gasoline and b) fuel cells. The use of it by the first method requires pure oxygen to be used for combustion; it is an expensive method involving oxygen storage and transportation. If oxygen is substituted by air in the combustion, it produces nitrogen oxides that are defying the definition of clean energy. The other method is to use it as a fuel cell for easy emission free transportation. Here chemical energy is converted to electrical energy directly in a fuel cell. To illustrate principles of related fuel cells, methanol and borohydride fuel cells are included in this manual. The nine experiments described here are designed for illustrating the concepts for the beginners and those motivated to go for clean energy.'--Provided by publisher.
Title from PDF file title page (viewed March 23, 2016).
Includes bibliographical references.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Hydrogen as fuel -- Laboratory manuals; Fuel cells -- Laboratory manuals; Electronic books